(3TQM bUjOI GHf YHOhfs - (3YHO Gdedc Hf YHO Gddg Hf HOQhf GdMVQeis; (3eMeO YHO GdeLjO GdagQj, GHf YHOhf,J (B520 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPi CaGV Ydi CdSfJfG eGFjI GdHjGf aEfg LeYfi aCfTO CMO GdMGVQjf bUjOI GHf YHOhf GdJi fOH HgG Hfi SdeI GdeYQhajf HHfi GdCaWS ahdYJ Cf ChQi bOMgG s
(3BNQgG (B:s
(3adeG NQL LYd CUMGHg jJSddhf efg MJi Hbi hMOg abUOg QLd CShO hgfG GfJgi HGdcdGe ai TQM GdbUjOI, Ke Cfg deG PcQ ced ef PcQ ef GdCee GdNGdjI s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1329s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs